TRANSPARANSI PELAYANAN PUBLIK PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA PEKANBARU - harsini, harsini (Jurnal Niara, 2018)
The purpose of this research is to analyze the transparency and to analyze the factors that inhibit the creation of transparency of public service to the investment service and integrated service one door of Pekanbaru City. In this study using qualitative data analysis, that is by conducting data analysis through surveys, interviews and through information obtained in the field. Based on the results of research that the transparency of information service has not been fully transparent in the provision of services to the community. Priority interest of service users has not been fully prioritized. This can be seen from the management of public service that has not been published to the public, such as the cost and service time that is still not kept on the customer, and this is caused by the lack of resources available in the field of IMB management